1996
DOI: 10.7863/jum.1996.15.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler sonographic assessment of placental circulation in the first trimester of normal pregnancy.

Abstract: Our aim was to study placental circulation during the first trimester of normal pregnancy. For this purpose, 108 single pregnancies from 4 to 15 gestational weeks were evaluated through conventional Doppler ultrasonography. The flow velocity waveforms from the retrochorionic arteries (spiral-radial arteries) and the umbilical artery were assessed using the peak systolic velocity, resistive index, and pulsatility index). Intervillous flow velocity waveform was evaluated from the maximum velocity. The earliest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
29
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 11 publications
(11 reference statements)
7
29
0
1
Order By: Relevance
“…First, we choose to use placentae of 12-week gestation. This was because there is evidence suggesting that the oxygen concentration around the human placenta increases near the end of the first trimester of pregnancy when the trophoblast plugs in the spiral arteries dissipate, allowing maternal blood to enter the intervillous space (Rodesch et al, 1992;Merce et al, 1996;Jaffe, 1998;Watson et al, 1998;Jauniaux et al, 2000). Furthermore, we have recently shown, by studying >3500 explants from placentae ranging from 8 to 12 weeks of gestation, that although oxygen concentration affects the behaviour of trophoblasts from placentae of 10-week gestation or less, there is little or no effect of oxygen concentration on explants from placentae of ≥11-week gestation (James et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First, we choose to use placentae of 12-week gestation. This was because there is evidence suggesting that the oxygen concentration around the human placenta increases near the end of the first trimester of pregnancy when the trophoblast plugs in the spiral arteries dissipate, allowing maternal blood to enter the intervillous space (Rodesch et al, 1992;Merce et al, 1996;Jaffe, 1998;Watson et al, 1998;Jauniaux et al, 2000). Furthermore, we have recently shown, by studying >3500 explants from placentae ranging from 8 to 12 weeks of gestation, that although oxygen concentration affects the behaviour of trophoblasts from placentae of 10-week gestation or less, there is little or no effect of oxygen concentration on explants from placentae of ≥11-week gestation (James et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Merce et al [7], studying 108 pregnancies of between 4 and 15 weeks, evidenced venous-like intervillous flow, starting from the end of the 5th week. In our study concerning normal ongoing pregnancies, we could detect in all cases a nonpulsatile intervillous flow, starting from 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, morphoradiological examination of three hysterectomy specimens at 8, 9, and 13 weeks showed that cytotrophoblastic plugs completely obstructed the spiral arteries and prevented maternal blood from penetrating into the intervillous space before 12 weeks of gestation [5]. However, recent studies using more sensitive Doppler imaging have shown the presence of intervillous flow as early as the 1st trimester in normal pregnancies [6,7] and have raised questions about the role of trophoblastic plugs in the uteroplacental circulation. These discrepancies may be explained by differences in the sensitivity of the machines, but also by variation in the analysis of the detected flows.…”
Section: Introductionmentioning
confidence: 99%
“…Independent Doppler studies from three institutions using sensitive conventional and power Doppler velocimetry found that continuous and pulsatile blood flow can be extracted from intervillous space in both normal pregnancies and those with adverse outcome. [63][64][65] Data presented by Kurjak and Kupesic 61 support the concept that establishment of the intervillous circulation is a progressive process during the first trimester of pregnancy. Between the 6th and 10th week of gestation clear blood flow signals are derived from the walls of the yolk sac supporting the hypothesis that yolk sac is responsible for optimal delivery of nutrients and oxygen to developing embryo up to 10 weeks of gestation.…”
mentioning
confidence: 78%